The Cambridge introduction to narrative - Abbott, H. Porter, 1940- (Cambridge University Press, 2021)
"The purpose of this book is to help readers understand what narrative is, how it is constructed, how it acts upon us, how we act upon it, how it is transmitted, how it changes when the medium or the cultural context change, and how it is found not just in the arts but everywhere in the ordinary course of people's lives, many times a day. This book grounds its treatment of narrative by introducing it as a human phenomenon that is not restricted to literature, film, and theatre, but is found in all activities that involve the representation of events in time. At the same time, the book honors the fact that out of this common capability have come rich and meaningful narratives that we come back to and reflect on repeatedly in our lives. In organization, the book introduces the subject of narrative by moving outward from simplicity to complexity, from the component parts of narrative to its numerous effects, including its extraordinary rhetorical power, and thence to issues of interpretation, what happens when works are adapted across media, and the ways in which we think and interact through narrative"- Resumé vydavatel
Keywords: naratologie; vypravěčské techniky; vyprávění; narratology; narrative techniques; storytelling; monografie; monographs